Comparison between Genetic Algorithm and Prey-Predator Algorithm. - Ong, Hong Choon
The use of metaheuristic algorithms to different problems becomes very common after the introduction of genetic algorithm in 1975. Most of these algorithms are inspired by real life biological phenomenon. We introduce a new metaheuristic algorithm inspired by prey-predator interaction of animals. In the algorithm, randomly generated solution are assigned as a predator and preys depending on their performance on the objective function. We also compared the performance of this algorithm with the genetic algorithm on selected test problems and we showed that the new algorithm performed better in our publication.